Structural Elucidation and Antibacterial Activity Studies of Leaf Extracts of Withania somnifera - Amsalu Genanaw Gebeyehu; Kumlachew Zelalem Walle; Meseret ZEbeaman Birhanu; Rahel Gebeyehu (Universitas Gadjah Mada, 2022)
Withania somnifera (W. somnifera), a small, woody shrub in the Solanaceae family, has been studied using a phytochemical test, antibacterial activity and partial characterizations. Air-dried and powdered leaves of the plant were extracted with maceration over an electrical shaker using the solvent chloroform and methanol. After crude extracts of the plant were concentrated, the diffusion antibacterial susceptibility test was carried out on 25, 50, 75, and 100 mg/mL of chloroform and methanol crude extract. The bacteria used were S. aureus, S. pneumonia, E. coli, and S. typhi. Each antibacterial activity test was carried out three times. The most active crude extract of the plant was subjected to a phytochemical test and fractionation with column chromatography. Chloroform and methanol extract of the plant inhibits all cultures of four bacteria. Both chloroform and methanol extract of W. Somnifera inhibits both gram-positive and negative bacterium with a comparable inhibition zone with the standard antibiotics, amoxicillin, gentamicin, and cefoxitine. In addition, it gives a maximum inhibition zone than that of amoxicillin, starting from 25 to 100 mg/mL. Methanol extract of W. somnifera contains phenolic, alkaloids, flavonoids, tannins, and phytosteroids. Partial characterization of pure fractions by using 1H-NMR, 13C-NMR, Dept-135 NMR, and IR spectroscopy, the compound WS-1 affords withaferin A. Withaferine A shows antibacterial activity with an inhibition zone of 11, 10.5, 11, and 9 mm against the bacterium S. aureus, S. pneumoniae, E. coli, and S. typhi respectively.